AB0205 Unusual aetiology of erythema nodosum, arthritis, and pleural effusion. (1st June 2001) - Steiger, U; Weber, M; Gerber, H
Abstract : Background: Association of erythema nodosum with giardia lamblia infection is only known for a few adult cases in the literature. 1 Several case reports discuss reactive arthritis or sacroiliitis with giardiasis. 2 Allergies and other immunological features such as pleural eosinophilic effusion have occasionally been reported as well. Objectives: A 36-year-old male refugee from Sri Lanka was referred to our outpatient department for erythema nodosum and history of arthralgia of large and medium-size joints and low back pain not fully responsive to NSAID. He also had symptoms such as low grade fever, conjunctival injection, and headaches. He complained of a slight weight loss. Family history and system review was unremarkable except for intermittent chronic eye inflammation with itching, later classified as nodular episcleritic lesions. There were no gastrointestinal complaints. Methods: Clinical examination revealed erythema nodosum and pleural effusion, but no synovialitis. Laboratory analysis showed mild inflammatory reaction with normal eosinophil count, no complement consumption nor significant auto-antibody titer. Serum IgE titer was high. Three-phase bone scintigraphy and x-ray of the sacroiliacal joints were normal. Chest x-ray showed a pleural effusion. Because of life style and origin of the patient, we ordered a stool sample examination, which was full of giardia lamblia. Results: The prescribed metronidazole regimen was not taken for compliance problems. Five months later he was again referred for erythema nodosum and arthritis with swelling of ankle, wrist, knee and MCP joints. Chest x-ray revealed pleural effusion as before. Stool samples again showed giardia infestation with unchanged laboratory analyses. After a five days course of metronidazole 250 mg t.i.d., joint symptoms diminished dramatically, and erythema nodosum vanished. Conclusion: Giardia lamblia infection typically presents with abdominal symptoms or malabsorption syndrome, some patients develop low grade fever and headaches. Hypersensitivity symptoms such as pleural effusion, reactive arthritis and erythema nodosum are very rarely reported. Diagnosis is confirmed by the good response of the joint symptoms to antiparasitic therapy. The presented case of relapsing erythema nodosum and arthritis and pleural effusion documents for the first time in the literature the coincidence of these three rare complications of giardiasis. References: Giordano N, Fioravanti A, Mariani A, Marcolongo R. Erythema nodosum and giardia intestinalis. Clin Rheumatol. 1985;4:481–3 Tupchong M, Simor A, Dewar C. Beaver fever ? a rare cause of reactive arthritis. J Rheumatol. 1999;26:2701–2